HUBUNGAN ANTARA LOCUS OF CONTROL DAN KEMAMPUAN EMOSIONAL DENGAN KEADILAN PROSEDURAL: STUDI KORELASI TERHADAP GURU SD SWASTA KECAMATAN PONDOK GEDE BEKASI - Dieny Hafiza (Universitas Negeri Jakarta, 2016)
This research is aimed to investigate the relationship of (1) locus of control and procedural justice, (2) emotional ability and procedural justice, (3) locus of control and emotional ability all together with procedural justice of teachers in private elementary school subdistrict Pondokgede Bekasi. In data analysis, this research used causal survey method by using correlational Technicque. This study uses sample from 120 teachers in 5 private elementary school in subdistrict Pondokgede who are selected by using Multistage Simple Random Sampling.The result of the study reveals that: first, there is a positive relationship between locus of control with procedural justice of teachers in school. Second, there is a positive relationship between emotional ability with procedural justice of teachers in school. And third, there is a positive relationship both of locus of control and emotional ability with procedural justice of teachers in school.